Analisis Percepatan Tanah Maksimum (PGA) dan Intensitas Skala Mercalli Menggunakan Data Mikrotremor dan Data Gempabumi di Wilayah Pesisir Kecamatan Moramo - La Hamimu; Laode Ihksan Juarzan; Sugi Astira (Program Studi Teknik Geofisika FITK UHO, 2025)
Research has been carried out in the Coastal area of Moramo District, South Konawe Regency. This study aims to determine the distribution of values for the dominant period , Peak ground acceleration (PGA), and seismic intensity based on the MMI scale using earthquake data that occurred in Southeast Sulawesi over a period of 30 years from 1993 to 2023 to be exact. Microtremor data were analyzed using the HVSR method with geopsy software to obtain the dominant frequency value , which then determines the dominant period value to obtain the peak ground acceleration (PGA) value so that the seismic intensity value can be determined. The dominant period values obtained ranged from 0,07 to 0,99 s while the surface PGA values obtained ranged from 35,32 to 149,29 gal and the basement PGA ranged from 30,23 to 44,92 gal. The seismic intensity values obtained ranged from 3,44 to 4,35 SR. The seismic intensity values is then classified in the form of a distribution map. The seismic intensity distribution map shows that the Coastal area of Moramo District, South Konawe Regency has a relatively low level of seismic intensity.